Дослідження впливу основних параметрів та умов експлуатації на оптимальне використання засобів механізації будівельною організацією - Шаляпіна, Т. С.; Назаренко, І. І. (Ways to Improve Construction Efficiency, 2014)
The influence of researched parameters and conditions for the optimal use of mechanization of construction enterprises in terms of actual use.